CO2 interaction with violarite (FeNi2S4) surfaces: a dispersion-corrected DFT study. Issue 31 (25th July 2018) - Posada-Pérez, Sergio; Santos-Carballal, David; Terranova, Umberto; Roldan, Alberto; Illas, Francesc; de Leeuw, Nora H.
Abstract : The interaction between the CO2 molecule and the violarite FeNi2 S4 001 and 111 surfaces is studied using different exchange–correlation functionals and long-range dispersion correction approximations. Abstract : The unbridled emissions of gases derived from the use of fossil fuels have led to an excessive concentration of carbon dioxide (CO2 ) in the atmosphere with concomitant problems to the environment. It is therefore imperative that new cost-effective catalysts are developed to mitigate the resulting harmful effects through the activation and conversion of CO2 molecules. In this paper, we have used calculations based on the density functional theory (DFT), including two semi-empirical approaches for the long-range dispersion interactions (-D2 and -D3), to explore the interaction of CO2 with the surfaces of spinel-structured violarite (FeNi2 S4 ). This ternary sulfide contains iron ions in the highest possible oxidation state, while the nickel atoms are in the mixed 2+/3+ valence state. We found that CO2 interaction with violarite is only moderate due to the repulsion between the oxygen lone pairs and the electronic clouds of the sulfur surface atoms. This suggests that the CO2 activation is not dictated by the presence of nickel, as compared to the pure iron-isomorph greigite (Fe3 S4 ). These results differ from findings in (Ni, Fe) ferredoxin enzymes, where the Ni/Fe ratio influences the redox potential, which suggests that the periodic crystal structure of violarite may hinder its redox capability.